Как это решать? после этого: 2cosx(1+2sinx)=4sin^2 x-1

Как это решать? после этого: 2cosx(1+2sinx)=4sin^2 x-1
Гость
Ответ(ы) на вопрос:
Гость
2cosx(2sinx+1) =(2sinx+1)(2sinx-1) ; 2cosx(2sinx+1) -(2sinx+1)(2sinx-1) =0; (2sinx+1)(2cosx -2sinx+1) =0 ; a) 2sinx+1 =0  ; sinx = -1/2 ; x=(-1)^(n+1)*π/6 +π*n ,n∈Z. б) 2cosx -2sinx+1 =0 ; sinx -cosx =1/2 ; √2sin(x-π/4) =1/2; x-π/4 =  (-1)^n*arcsin1/(2√2)+π*n,  n∈Z. x = π/4+ (-1)^n*arcsin1/(2√2)+π*n,  n∈Z.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы